Blake Edwards : interviews - Edwards, Blake, 1922-2010 (Conversations with filmmakers series., 2018)
A long-overdue collection of interviews with the multitalented and versatile writer, director, and producer of such films as Days of Wine and Roses, Breakfast at Tiffany's, and Victor/Victoria.